Restoration of Good Name Towards Victims of Online Defamation as a Form of Cyberbullying - Ni Made Padmawardhani Rakheswari (Westscience Press, 2026)
With the pervasive use of digital platforms, online defamation has emerged as a prominent form of cyberbullying, threatening individuals’ reputations, psychological well-being, and social credibility. This study investigates mechanisms for restoring the good name of victims of online defamation, emphasizing legal, social, and psychological interventions. Using a mixed-method approach, quantitative data were collected from 300 social media users who experienced defamation, while qualitative interviews explored personal experiences, coping strategies, and social reintegration. Data analysis employed Structural Equation Modeling–Partial Least Squares (SEM-PLS) to evaluate relationships among online defamation, psychological impact, social support, restorative strategies, digital literacy, and perceived reputation recovery. Findings indicate that social support, digital literacy, and restorative justice interventions significantly enhance reputation restoration, with victims who received legal action, public acknowledgment, and community support reporting the most effective outcomes. Grounded in Cyberbullying Theory, Reputation Management Theory, and Restorative Justice Theory, the study provides a comprehensive framework linking individual psychological resilience, social perception, and restorative mechanisms. The results highlight the importance of culturally sensitive approaches, including social norms, online ethics, and communication strategies tailored to specific communities. These insights inform policy design, platform governance, and educational programs aimed at mitigating online defamation, empowering victims, and promoting digital literacy. The study contributes to theory by integrating social, legal, and psychological perspectives on reputation restoration, and to practice by offering actionable strategies for victims, policymakers, and digital platform managers.